Network Physiology: Mapping interactions between complex physiological systems - Ivanov, Plamen Ch. (My University, 2016)
The human organism is an integrated network where multi-component organ systems, each with its own regulatory mechanisms, continuously interact to optimize and coordinate their function. Organ-to-organ interactions occur at multiple levels and spatiotemporal time scales to produce distinct physiologic states: wake and sleep; light and deep sleep; consciousness and unconsciousness. Disrupting organ communications can lead to dysfunction of individual systems or to collapse of the entire organism. Yet, we know almost nothing about the nature of the interactions between diverse organ systems and their collective role in maintaining health. We propose a framework to probe dynamical interactions among physiological systems, and we identify a physiological network. We find that each physiological state is characterized by a specific network structure, demonstrating a robust interplay between network topology and physiologic function. Across physiological states, the network undergoes topological transitions associated with fast reorganization of physiological interactions on time scales of a few minutes, indicating high network flexibility in response to perturbations. The proposed system-wide integrative approach facilitates the development of a new field, Network Physiology
Keywords: Fisiología; Física aplicada; Network physiology